Expression analysis of liver-specific circulating micrornas in hcv-induced hepatocellular carcinoma in Egyptian patients - Mourad, Lobna Mohamed (AUC Knowledge Fountain, 2018)
Introduction: The prevalence of hepatocellular carcinoma (HCC) in Africa is higher compared to the rest of the world due to the high incidence of chronic infection with hepatitis C virus (HCV). In Egypt, HCV infection is the leading cause for the high HCC incidence, which is usually diagnosed at late stages. Due to the absence of reliable and accurate biomarkers for early detection of liver cancer, circulating microRNAs have recently emerged as great candidates for early diagnosis of HCC. These small non-coding RNA molecules are responsible for regulating gene expression and RNA stability. Therefore, the aim of this study is to investigate the potential of liver-specific circulating microRNAs as an accurate non-invasive diagnostic tool for the early detection of HCV-induced HCC. Methods: Eight main miRNAs (miR-16, miR-34a, miR-122a, miR-125a, miR-139, miR-145, miR-199a, and miR-221) were selected due to their expression patterns in HCC as well as their contribution to the development of hepato-carcinogenesis. A total of 165 patients were enrolled in this study, from which serum samples were collected and categorized into four main patient groups: 42 chronic hepatitis C (CHC) without cirrhosis, 45 CHC with cirrhosis (LC), 38 HCC with HCV patients, and 40 healthy controls. The expression profile of the eight miRNAs was analyzed using TaqMan real-time reverse transcription-polymerase chain reaction. Additionally, the conventional markers for HCC Î±-fetoprotein (AFP) and des-Î³-carboxyprothrombin (DCP) were measured using commercial kits. Results: Serum levels of miRNA-122a, miRNA-125a, miRNA-139, miRNA-145 and miRNA-199a were significantly lower (p<0.01) in HCC than in both CHC and LC groups. On the other hand, no significant difference was shown in the expression of miR-16, miR-34a, and miR-221 between the CHC, LC, and HCC groups. MiR-16, miR-34a, and miR-221 were significantly elevated in the HCC group compared to the control group. MiR-122a showed the highest specificity and sensitivity, followed by miR-125a, which had the second highest specificity, indicating its significance in diagnosis. Conclusions: The results indicated that measurement of serum levels of miR-122a, miR-125a, miR-139, miR-145, and miR-199a can help to differentiate HCC from CHC and LC. Measurement of serum levels of miR-16, miR-34a, and miR-221 were shown to have a prognostic value. Highly significant correlation was established between different miRNAs within the same patient group or between two different groups, indicating a great diagnostic value for the early detection of HCC. MiR-122a had the highest specificity and sensitivity, indicating that serum miR-122a might serve as a novel and potential non-invasive biomarker for HCV-induced HCC.